2007
DOI: 10.1037/h0100388
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral parent-training approaches for the treatment of bedtime noncompliance in young children.

Abstract: Bedtime noncompliance is one of the most common and treatable types of child sleep problems. Children who are noncompliant at bedtime are more likely to exhibit daytime somnolescence, which may in turn lead children to exhibit daytime misbehavior, impaired social functioning and poorer school achievement. In addition, these bedtime problems can have a number of negative consequences for members of the child's family, including parental sleep deprivation and depression. Behavioral parent-training approaches are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…Parental resistance remains the largest barrier to the implementation of extinction interventions, 30 and preliminary data 28 would suggest the majority of Australian parents find graduated extinction too difficult and stressful to implement. Despite being a known issue for decades, few researchers have explicitly addressed it.…”
Section: Sum M Ary and Conclusi Onsmentioning
confidence: 99%
See 3 more Smart Citations
“…Parental resistance remains the largest barrier to the implementation of extinction interventions, 30 and preliminary data 28 would suggest the majority of Australian parents find graduated extinction too difficult and stressful to implement. Despite being a known issue for decades, few researchers have explicitly addressed it.…”
Section: Sum M Ary and Conclusi Onsmentioning
confidence: 99%
“…Underlying extinction interventions is the premise that bedtime noncompliance has been trained by the behaviors of the parents. 30 But it would be unwise to assume all child sleep problems have been trained by the parents. Some data suggests maladaptive parenting behaviors can follow early infancy sleep difficulties, not the other way around.…”
Section: Misinformationmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have found untreated sleep problems to be associated with childhood behavior problems (Adams & Rickert, 1989;Ortiz & McCormick, 2007;Wade, Ortiz, & Gorman, 2007). Developmental psychologists often categorize problem behaviors as being either externalizing or internalizing.…”
Section: Impact Of Sleep Problems On Child Developmentmentioning
confidence: 99%